Trading fair for free: is there justification for widened pharmaceutical intellectual property protection under Australia-US Free Trade Agreement? - Lim, David; Fitzgerald, Tomas; Lewis, Janice (NPS, 2012)
Objective: The debate on the extent intellectual property protection should be used to reward innovation in pharmaceuticals is not new. In Australia, our patent regime for pharmaceuticals is moderated by mechanisms to control price (e.g. Pharmaceutical Benefits Scheme) and to stimulate local production (e.g. National Medicines Policy). Australia recently signed the Australia-US Fair Trade Agreement [2005] in which evergreening of pharmaceuticals is encouraged. The purpose of this paper is to provide a framework for and against evergreening as informed by international law and public health policy. Methods: A systematic review of legal indexing databases and reference lists from selected papers and case law were the source of data. Inclusion criteria were papers and decisions published in English, between 1990 and 2011. Results: The 12 commonly given reasons for extended intellectual property protection is grounded on the premise of rewarding pharmaceutical industry for investing in economic utility and compensate for economic harms in investing in new pharmaceuticals. Arguments against extended pharmaceutical intellectual protection appears to rest in natural rights whereby the right to health through pharmaceuticals is an inalienable human rights. Conclusion: There is currently insufficient incentive for research and development into orphaned diseases due to volume. To compensate the inventors of pharmaceuticals for orphaned diseases, there may be a justification for a tier-system of patenting pharmaceuticals based on prevalence of disease.